Akt2 Regulates Expression of the Actin-Bundling Protein Palladin - Chin, Y. Rebecca (2010)
The PI 3-K/Akt pathway is responsible for key aspects of tumor progression, and is frequently hyperactivated in cancer. We have recently identified palladin, an actin-bundling protein that functions to control the actin cytoskeleton, as an Akt1-specific substrate that inhibits breast cancer cell migration. Here we have identified a role for Akt isoforms in the regulation of palladin expression. Akt2, but not Akt1, enhances palladin expression by maintaining protein stability and upregulating transcription. These data reveal that Akt signaling regulates the stability of palladin, and further supports the notion that Akt isoforms have distinct and specific roles in tumorigenesis.